2008
DOI: 10.1556/avet.56.2008.3.13
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification of in vitro matured oocytes of Mangalica and Large White pigs

Abstract: The breeding of Mangalica, a native pig breed in Hungary, had been started in 1833, but this pig breed almost became extinct in Hungary in the past decades. In 1991, the number of sows was only 200. Although in these days the existing Mangalica population consists of more than 6000 animals representing different colour variations, the preservation of this traditional pig breed is still very important. Vitrification is a potential tool for the preservation of gametes and embryos of these animals. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, despite of high survival rates, vitrified M-II stage oocytes generally show poor developmental competence in terms of blastocyst formation rates and cell numbers in blastocysts [18]. Furthermore, most studies describing blastocyst production from vitrified porcine M-II stage oocytes used parthenogenetic activation to generate embryos [23, 28,[37][38][39], whereas other studies using IVF often reported the failure of embryo development [21,[40][41][42][43]. Similarly, in our laboratory, we have succeeded in the generation of blastocysts from vitrified M-II stage oocytes by parthenogenetic activation [25], whereas IVF of the M-II stage oocytes vitrified by the same method did not result in blastocyst development [27].…”
mentioning
confidence: 99%
“…However, despite of high survival rates, vitrified M-II stage oocytes generally show poor developmental competence in terms of blastocyst formation rates and cell numbers in blastocysts [18]. Furthermore, most studies describing blastocyst production from vitrified porcine M-II stage oocytes used parthenogenetic activation to generate embryos [23, 28,[37][38][39], whereas other studies using IVF often reported the failure of embryo development [21,[40][41][42][43]. Similarly, in our laboratory, we have succeeded in the generation of blastocysts from vitrified M-II stage oocytes by parthenogenetic activation [25], whereas IVF of the M-II stage oocytes vitrified by the same method did not result in blastocyst development [27].…”
mentioning
confidence: 99%
“…Various protocols for the vitrification of porcine oocytes and embryos have been reported, and the development of a standardized (optimum) protocol would be beneficial for each. To date, oocyte cryopreservation for gene banking has only been reported in two local breeds (Varga et al, 2008;Somfai et al, 2019).…”
Section: Oocyte Cryopreservation Techniquesmentioning
confidence: 99%
“…If piglet production using an IVP system could be available for indigenous breeds, it would be advantageous for the preservation of genetic resources or breeding activities. Although, to our knowledge, this has not yet been reported, IVP has been established for some indigenous pig breeds (Nguyen et al, 2015;Varga et al, 2008),…”
mentioning
confidence: 93%